Relaciones étnico-lingüísticas de los palenques en el Perú. - Cajavilca Navarro, Luis (2008)
The African cultural activity in Peru is focused on the ethnic group family: Art, music, religion and ancestral literature that reinforced their social identity. In Peru just like in all of the provinces of the New World the mix of races was strongly developed between the groups of: white people, Indians, and black people. The contact of the black people with the Indian population favored the syncretism of the mix of the African race. The «palisade» in Peru kept certain characteristic of africanity, meanwhile, this stood as bastion of the resistance against the culture that was imposed by the colonizer until the XIX century